A "Pre‐Constrained Metal Twins" Strategy to Prepare Efficient Dual‐Metal‐Atom Catalysts for Cooperative Oxygen Electrocatalysis. Issue 7 (11th January 2022) - Liu, Ming; Li, Na; Cao, Shoufu; Wang, Xuemin; Lu, Xiaoqing; Kong, Lingjun; Xu, Yunhua; Bu, Xian‐He
Abstract: Dual‐metal‐atom‐center catalysts (DACs) are a novel frontier in oxygen electrocatalysis, boasting functional and electronic synergies between contiguous metal centers and higher catalytic activities than single‐atom‐center catalysts. However, the definition and catalytic mechanism of DACs configurations remain unclear. Here, a "pre‐constrained metal twins" strategy is proposed to prepare contiguous FeN4 and CoN4 DACs with homogeneous conformations embedded in a N‐doped graphitic carbon (FeCo‐DACs/NC). A programmable phthalocyanines dimer is used as a structural moiety to anchor the bimetallic sites (containing Co and Fe) in a metal–organic framework (MOF) to achieve delocalized dispersion before pyrolysis. The resultant FeCo‐DACs/NC exhibits excellent electrochemical performance in oxygen electrocatalysis and rechargeable Zn–air batteries. Theoretical calculations demonstrate that the synergetic interaction of adjacent metals optimizes the d‐band center position of metal centers and balances the free energy of the *O intermediate, thereby improving the oxygen electrocatalytic activity. This work opens up an avenue for the rational design of DACs with tailored electronic structures and uniform geometric configurations. Abstract : A "pre‐constrained metal twin" strategy is presented for the first time to prepare dual‐metal‐atom‐center catalysts (FeCo‐DACs/NC) with continuous FeN4 and CoN4 . The FeCo‐DACs/NC delivers excellent catalytic activity in oxygen evolution reaction, oxygen reduction reaction, and Zn–air batteries. The synergistic effect between the two metals optimizes the free energy of the oxygen intermediate state, resulting in improved performance.